PP124 Smart Capability Building For Effective Patient Involvement. (2019) - Davis, Claire; Hughes, Sophie; Myles, Susan
Abstract : Introduction: A new Health Technology Assessment (HTA) agency, Health Technology Wales (HTW), has been established to consider the identification, appraisal, and adoption of non-medicine health technologies. This includes, for example, medical devices, surgical procedures and diagnostics. HTW recognizes the importance of effective patient and public involvement (PPI) and is building smart capabilities. Methods: HTW consulted with external organizations to identify the first steps toward effective PPI. Public partners were recruited as a priority before working together on a PPI strategy. Building smart capabilities is key to establishing effective PPI and future-proofing. HTW established a PPI Standing Group to inform HTW throughout its work, including the development of processes and procedures. Results: Knowledge and resources have been shared and future collaborations identified, including events to encourage new topics from patients and the public. The HTW PPI lead has become a member of key PPI groups, locally and internationally. HTW has recruited public partners who are actively contributing as full members of the Assessment Group and the Appraisal Panel; two members on each Committee. The PPI Standing Group has been established. They have provided advice and co-produced PPI tools for piloting. Conclusions: The PPI Standing Group concluded that PPI methods and approaches should be tailored for each project based on best practice, and should be piloted to allow them to evolve based on impact evaluation. A PPI strategy or framework would be more useful at a later stage. HTW is committed to identifying and following best practice. Future-proofing and building smart capability will be key to ensuring that HTW develops effective PPI that can be dynamic and responsive to the evolving PPI and HTA landscapes.